Lightweight alkali slag tough material for reinforcing structure in cold region
By using lightweight alkaline slag tough materials prepared by industrial waste slag and other industrial by-products, the problems of high energy consumption, serious pollution and low solid waste utilization are solved in traditional cement reinforcement materials, and efficient, environmental protection and resource reinforcement in cold zone structures are achieved. Requirements for utilization.
Patent Information
- Application Number
- CN202411492877.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional silicate cement reinforcement materials have problems such as high energy consumption, serious pollution and low solid waste utilization in their applications, which are difficult to meet the needs of structural reinforcement in cold areas.
Light alkali slag tough materials composed of industrial waste slag, potassium water glass, sodium hydroxide, fly ash, hollow glass microbeads, quartz sand and polypropylene fibers are prepared through alkali excitation and reinforced with fibers, combined with hollow glass microbeads The material used for structural reinforcement in cold zone was prepared.
It realizes excellent mechanical and working performance of the material, such as lightweight, high strength, thermal insulation, and frost resistance, reduces energy consumption and pollution, effectively utilizes industrial solid waste, and solves the problems of high self-weight and low added value of traditional materials.
Smart Images

Figure CN119461963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a lightweight alkali slag toughness material for reinforcing structures in cold regions. Background Art
[0002] Traditional silicate cement reinforcement materials are widely used, but they need to go through the cumbersome process of "two grindings and one burning", which produces a lot of noise, dust, greenhouse gas CO2 and toxic gases, which seriously pollute the environment. According to the "2023 China Building Energy Consumption and Carbon Emission Research Report", the total carbon emissions from construction and construction in China in 2022 will be 5.08 billion tons, accounting for 50.9% of the national carbon emissions, of which carbon emissions in the construction production stage will reach 2.82 billion tons. In order to control the emission of greenhouse gases in the construction process, two directions need to be focused on: one is to reduce the energy consumption of building production and operation, and the other is to use renewable resources. In 2022, the total energy consumption of construction and construction will be 2.27 billion tons of standard coal, accounting for 45.5% of the total energy consumption in the country, of which energy consumption in the building operation stage will account for 21.3%. Efficiently improving the energy saving rate in the production and operation stages of buildings is an important engine for my country to achieve the "dual carbon" goal.
[0003] At the same time, the utilization rate of solid wastes such as red mud, slag, and steel slag in my country is still low, occupying a large amount of land resources and posing a great safety hazard to the ecological environment. According to data from the Ministry of Housing and Urban-Rural Development, the overall production of construction waste in my country from 2019 to 2023 is still on an upward trend, and it is expected that after 2024, the annual output will remain above 2.2 billion tons. Therefore, how to effectively utilize bulk solid waste has become a hot issue today. Studies have found that if alkali compounds or alkali-containing industrial waste (such as water glass, etc.) are used as activators to activate industrial waste slag (such as slag, red mud, etc.), supplemented with silica fume, fly ash, etc. for modification, and then added with hollow glass microspheres and fibers, a lightweight alkali slag toughness material (Lightweight alkali activated slag toughness material, referred to as LAASTM) can be obtained. LAASTM not only has the characteristics of lightweight, low energy consumption, and low pollution, but also has very excellent mechanical properties and seismic resistance.
[0004] The main raw materials of light alkaline slag toughness material are industrial waste slag (slag, red mud, steel slag, phosphorus slag, coal gangue, slag-like powder, etc.), silica fume, fly ash, potassium water glass, sodium hydroxide, quartz sand, hollow glass microspheres, polypropylene fiber, and water (tap water, seawater, etc.). With the rapid development of my country's steel industry, slag has become a huge industrial by-product. my country's annual slag output is 240 million tons, accounting for 50% of the global total output. For coastal areas, seawater can be electrodialyzed (using the selective permeability of anion and cation exchange membranes to anions and cations in water, under the action of an external DC electric field, a part of the ions in the water are transferred to another part of the water to achieve the purpose of desalination), so that seawater can be used in building materials, achieving the purpose of using local materials and greatly reducing transportation costs. Silica fume and fly ash are by-products of large industrial smelting and the main solid waste discharged from coal-fired power plants, respectively. Their material cost is low, and effective recycling can greatly reduce the pollution of waste to the environment. Hollow glass microspheres are specially processed glass microspheres with low density, high strength and good thermal insulation. Polypropylene fiber has the characteristics of high strength, good elasticity, wear resistance and corrosion resistance. The appropriate dosage can effectively improve the toughness and density of alkali slag materials. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies of the prior art, the present invention provides a lightweight alkali slag toughness material for cold region structure reinforcement.
[0007] (II) Technical solution
[0008] A lightweight alkaline slag toughness material for cold region structural reinforcement, comprising the following components: industrial waste slag, potassium water glass, sodium hydroxide, fly ash, hollow glass microspheres, quartz sand, and polypropylene fiber;
[0009] The mass ratio of industrial waste slag to potassium water glass is 1:0.248-0.286, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.062-0.071, the mass ratio of industrial waste slag to silica fume is 1:0.067-0.231, the mass ratio of industrial waste slag to fly ash is 1:0.200-0.385, the water-binder ratio is 0.38, 0.42, 0.44, the water content of the composite water glass after the sodium hydroxide and potassium water glass are mixed is 0.4838, when calculating the water consumption, the water content of the composite water glass should be deducted, and quartz sand is added according to the mortar-sand ratio of 2:1, 1:1, 1:2, the volume content of the hollow glass microspheres is 10%-20%, and the volume content of the polypropylene fiber is 0%-0.2%.
[0010] Preferably, the industrial waste residue is one of slag, red mud, steel slag, phosphorus slag, coal gangue and slag-like powder, or a mixture of several of them; and the water is tap water or sea water.
[0011] Preferably, the potassium water glass has an initial modulus of 2.76, a Baume degree of 46.3, a SiO2 content of 28.15%, a K2O content of 15.98%, and a density of 1.465 g / m 3 .
[0012] Preferably, the silica fume is a by-product of large-scale industrial smelting, has the appearance of gray or grayish white powder, has a refractoriness of >1600°C, and its main chemical components are: SiO2, Al2O3, Fe2O3, MgO, CaO, Na2O.
[0013] Preferably, the fly ash is secondary fly ash, which is the main solid waste discharged from coal-fired power plants, has a 45μm square hole sieve residue of no more than 20%, a water requirement ratio of no more than 105%, a loss on ignition of no more than 8%, a water content of no more than 2%, a sulfur trioxide content of no more than 3%, and its main chemical components are: SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2.
[0014] Preferably, the quartz sand is refined quartz sand with a specification of 10 to 40 meshes.
[0015] Preferably, the hollow glass microsphere model is domestic hollow glass microsphere 60, which is white in appearance and has a compressive strength of 12000 MPa.
[0016] Preferably, the polypropylene fiber has a size of 1 to 2 cm.
[0017] Preferably, the preparation method of the slag-like powder is as follows: add oxides to sea sand, calcine until melted, maintain the slag-water ratio at 1:10-1:15, water quench and granulate, crush the water-quenched slag, dry, grind and sieve, and sieve to a powder with a residue of no more than 10%, so as to obtain slag-like powder, and the particle size of the slag-like powder is 35-40 μm; the oxide is one or more of SiO2, CaO, Al2O3, MgO, Fe2O3; the mass ratio of sea sand to oxide is 3:1; the calcination temperature is 650-700°C.
[0018] Preferably, the method comprises the following steps:
[0019] S1. Weighing:
[0020] Weigh the industrial waste slag to potassium water glass at a mass ratio of 1:0.248-0.286, the industrial waste slag to sodium hydroxide at a mass ratio of 1:0.062-0.071, the industrial waste slag to silica fume at a mass ratio of 1:0.067-0.231, and the industrial waste slag to fly ash at a mass ratio of 1:0.200-0.385. The water-cement ratio is 0.38, 0.42, and 0.44. The water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838. When calculating the amount of water, the water content of the composite water glass should be deducted. The quartz sand is weighed at a cement-sand ratio of 2:1, 1:1, and 1:2. The volume content of the hollow glass microspheres is 10%-20%, and the volume content of the polypropylene fiber is 0%-0.2%.
[0021] S2, preparing mixed powder:
[0022] Industrial waste residue, silica ash, fly ash, hollow glass microspheres, polypropylene fiber and quartz sand are mixed and stirred to obtain a mixed powder;
[0023] S3. Adjust the modulus of potassium water glass:
[0024] Under stirring conditions, pour sodium hydroxide into potassium water glass and let it stand for 1 to 2 hours to obtain a composite potassium water glass solution;
[0025] S4. Place the mixed powder, composite potassium water glass solution, polypropylene fiber and water with different water-binder ratios in a mixer and stir them evenly, pour them into a steel mold, and then form them through high-frequency vibration on a concrete vibration table to obtain a lightweight alkali slag tough material for cold region structure reinforcement.
[0026] (III) Beneficial technical effects
[0027] 1. At present, traditional cement reinforcement materials are still widely used, and it is difficult to overcome the defects of high energy consumption, serious pollution, and energy shortage in cement production. The present invention is based on industrial waste slag, effectively combines industrial smelting waste and solid waste from coal-fired power plants, prepares alkali slag concrete through alkali excitation, and uses fiber to enhance the toughness and tensile strength of alkali slag concrete, inhibits material shrinkage, and limits the expansion of cracks. Finally, hollow glass microspheres are added to reduce the dead weight to prepare LAASTM for cold region structural reinforcement.
[0028] 2. Currently, adding hollow glass microspheres to LAASTM not only reduces the weight of the material while ensuring strength, but also effectively improves the thermal insulation and frost resistance of LAASTM due to the low thermal conductivity, good stability and strong water resistance of hollow glass microspheres. Therefore, compared with ordinary concrete, LAASTM presents excellent mechanical and working properties such as light weight, high strength, thermal insulation and frost resistance.
[0029] 3. The present invention investigates the influence of key parameters on the mechanical properties (compressive strength, flexural strength) and density of LAASTM used for cold region structural reinforcement by changing key parameters (silica fume content, fly ash content, water content, quartz sand content, hollow glass microsphere content, polypropylene fiber content). The test results show that LAASTM not only improves the problems of low strength and heavy weight of traditional cement reinforcement materials, but also solves the severe challenges of large-scale solid waste in my country, such as high difficulty in utilization, high processing cost, and low added value of comprehensive utilization products, and alleviates the problems of shortage of some natural materials and serious environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the LAASTM standard cube weighing chart for cold region structure reinforcement prepared according to Example 12.
[0031] Figure 2 Failure diagrams of LAASTM and ordinary concrete standard cubic compressive specimens: (a) shows LAASTM prepared in Example 12, and (b) shows ordinary concrete.
[0032] Figure 3 Cross-sectional views of LAASTM and ordinary concrete flexural test specimens: (a) shows LAASTM prepared in Example 8, (b) shows LAASTM prepared in Example 12, (c) shows LAASTM prepared in Example 13, and (d) shows ordinary concrete.
[0033] Figure 4 Appearance of the LAASTM standard cube after freeze-thaw cycles: (a) shows the LAASTM prepared by the ratio of Example 12 after 25 freeze-thaw cycles, (b) shows the LAASTM prepared by the ratio of Example 12 after 50 freeze-thaw cycles, and (c) shows the LAASTM prepared by the ratio of Example 12 after 75 freeze-thaw cycles.
[0034] Figure 5 The manufacturing process of LAASTM reinforced concrete columns for cold region structure reinforcement prepared using the mix ratio of Example 12 includes: (a) tying steel cages to the original columns, (b) the original column maintenance process, (c) the original column surface polishing, and (d) manufacturing the formed reinforced columns. DETAILED DESCRIPTION
[0035] Example 1: A method for preparing a lightweight alkali slag toughness material for cold region structural reinforcement, the proportion of the amount is a set of 40mm×40mm×160mm triple pieces, the total amount of cementitious material is 800g. The specific operation is as follows:
[0036] 1. Weighing materials:
[0037] Weigh the industrial waste slag to potassium water glass at a mass ratio of 1:0.248, the industrial waste slag to sodium hydroxide at a mass ratio of 1:0.062, the industrial waste slag to silica fume at a mass ratio of 1:0.067, and the industrial waste slag to fly ash at a mass ratio of 1:0.267. Among them, the water-cement ratio is 0.38 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water dosage), the mortar-sand ratio is 2:1, and the volume content of hollow glass microspheres is 20%;
[0038] The industrial waste residue described in step 1 is slag;
[0039] The silica fume described in step 1 is highly active microsilica powder, which is a by-product of large-scale industrial smelting;
[0040] The fly ash described in step 1 is secondary fly ash, which is the main solid waste discharged from coal-fired power plants;
[0041] The modulus of the potassium silicate described in step 1 is 1.0;
[0042] The quartz sand mesh number described in step 1 is 10 to 40 meshes;
[0043] The hollow glass microspheres described in step 1 are domestic hollow glass microspheres 60 model, with a compressive strength of 12000 MPa and a particle size of 60 meshes.
[0044] 2. Preparation of mixed powder:
[0045] Industrial waste residue, silica ash, fly ash, hollow glass microspheres and quartz sand were mixed and stirred for 1 minute to obtain a mixed powder;
[0046] 3. Adjust the modulus of potassium water glass:
[0047] Under stirring conditions, pour sodium hydroxide into potassium water glass and let it stand for 2 hours to obtain a potassium water glass solution;
[0048] Fourth, the mixed powder, composite potassium water glass solution, polypropylene fiber and water with different water-binder ratios are placed in a mixer and stirred evenly, poured into a steel mold, and then molded by high-frequency vibration on a concrete vibration table to obtain a lightweight alkali slag tough material for cold region structure reinforcement.
[0049] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structure reinforcement prepared in Example 1 are as follows: 28d average compressive strength is 83.45MPa, 28d average flexural strength is 8.9MPa, and density is 1917.24kg / m 3 .
[0050] Embodiment 2: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.266, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.066, the mass ratio of industrial waste slag to silica fume is 1:0.143, and the mass ratio of industrial waste slag to fly ash is 1:0.286. The other steps and parameters are the same as those in embodiment 1.
[0051] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 2 are as follows: 28d average compressive strength is 73.75MPa, 28d average flexural strength is 7.4MPa, and density is 1883.71kg / m 3 .
[0052] Embodiment 3: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.286, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.071, the mass ratio of industrial waste slag to silica fume is 1:0.231, and the mass ratio of industrial waste slag to fly ash is 1:0.308. The other steps and parameters are the same as those in embodiment 1.
[0053] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 3 are as follows: 28d average compressive strength is 70.90MPa, 28d average flexural strength is 6.8MPa, and density is 1883.44kg / m 3 .
[0054] Embodiment 4: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.248, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.062, the mass ratio of industrial waste slag to silica fume is 1:0.133, and the mass ratio of industrial waste slag to fly ash is 1:0.200. The other steps and parameters are the same as those in embodiment 1.
[0055] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 4 are as follows: 28d average compressive strength is 72.00MPa, 28d average flexural strength is 8.2MPa, and density is 1895.70kg / m 3 .
[0056] Example 5: The difference between this example and Example 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.286, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.071, the mass ratio of industrial waste slag to silica fume is 1:0.154, and the mass ratio of industrial waste slag to fly ash is 1:0.385. The other steps and parameters are the same as those in Example 1.
[0057] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 5 are as follows: 28d average compressive strength is 72.85MPa, 28d average flexural strength is 7.6MPa, and density is 1886.13kg / m 3 .
[0058] Example 6: The difference between this example and Example 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.266, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.066, the mass ratio of industrial waste slag to silica fume is 1:0.143, the mass ratio of industrial waste slag to fly ash is 1:0.286, and the volume content of hollow glass microspheres is 10%. Other steps and parameters are the same as those in Example 1.
[0059] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 6 are as follows: 28d average compressive strength is 71.10MPa, 28d average flexural strength is 8.4MPa, and density is 1994.49kg / m 3 .
[0060] Example 7: The difference between this example and Example 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.266, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.066, the mass ratio of industrial waste slag to silica fume is 1:0.143, the mass ratio of industrial waste slag to fly ash is 1:0.286, and the volume content of hollow glass microspheres is 15%. Other steps and parameters are the same as those in Example 1.
[0061] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 7 are as follows: 28d average compressive strength is 70.40MPa, 28d average flexural strength is 7.4MPa, and density is 1931.64kg / m 3 .
[0062] Embodiment 8: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste residue to potassium water glass is 1:0.266, the mass ratio of industrial waste residue to sodium hydroxide is 1:0.066, the mass ratio of industrial waste residue to silica fume is 1:0.143, the mass ratio of industrial waste residue to fly ash is 1:0.286, and the water-binder ratio is 0.42 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water consumption). Other steps and parameters are the same as those in embodiment 1.
[0063] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 8 are as follows: 28d average compressive strength is 75.80MPa, 28d average flexural strength is 7.1MPa, and density is 1856.25kg / m 3 .
[0064] Embodiment 9: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.266, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.066, the mass ratio of industrial waste slag to silica fume is 1:0.143, the mass ratio of industrial waste slag to fly ash is 1:0.286, and the water-binder ratio is 0.46 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water consumption). Other steps and parameters are the same as those in embodiment 1.
[0065] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 9 are as follows: 28d average compressive strength is 70.70MPa, 28d average flexural strength is 7.8MPa, and density is 1846.48kg / m 3 .
[0066] Embodiment 10: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.266, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.066, the mass ratio of industrial waste slag to silica fume is 1:0.143, the mass ratio of industrial waste slag to fly ash is 1:0.286, the water-binder ratio is 0.42 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water consumption), and the mortar-sand ratio is 1:1. Other steps and parameters are the same as those in embodiment 1.
[0067] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 10 are as follows: 28d average compressive strength is 63.20MPa, 28d average flexural strength is 7.5MPa, and density is 1954.18kg / m 3 .
[0068] Embodiment 11: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste slag to potassium water glass is 1:0.266, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.066, the mass ratio of industrial waste slag to silica fume is 1:0.143, the mass ratio of industrial waste slag to fly ash is 1:0.286, the water-binder ratio is 0.42 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water consumption), and the mortar-sand ratio is 1:2. Other steps and parameters are the same as those in embodiment 1.
[0069] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 11 are as follows: 28d average compressive strength is 67.00MPa, 28d average flexural strength is 8.5MPa, and density is 2081.25kg / m 3 .
[0070] Embodiment 12: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste residue to potassium water glass is 1:0.266, the mass ratio of industrial waste residue to sodium hydroxide is 1:0.066, the mass ratio of industrial waste residue to silica fume is 1:0.143, the mass ratio of industrial waste residue to fly ash is 1:0.286, the water-binder ratio is 0.42 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water dosage), and the volume content of polypropylene fiber is 0.1%. Other steps and parameters are the same as those in embodiment 1.
[0071] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 12 are as follows: 28d average compressive strength is 80.25MPa, 28d average flexural strength is 7.3MPa, and density is 1835kg / m 3 After 25 freeze-thaw cycles, the appearance was almost intact, and the compressive strength loss rate was only 5.89%. After 50 freeze-thaw cycles, the appearance was slightly damaged, and the compressive strength loss rate was 18.31%. After 75 freeze-thaw cycles, the appearance was obviously damaged, and the compressive strength loss rate reached 50%. In summary, it meets the requirements of the specification, and the frost resistance grade is ≥ F50, which can be called frost-resistant concrete.
[0072] Embodiment 13: The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of industrial waste residue to potassium water glass is 1:0.266, the mass ratio of industrial waste residue to sodium hydroxide is 1:0.066, the mass ratio of industrial waste residue to silica fume is 1:0.143, the mass ratio of industrial waste residue to fly ash is 1:0.286, the water-binder ratio is 0.42 (the water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838, and the water content of the composite water glass should be deducted when calculating the water dosage), and the volume content of polypropylene fiber is 0.2%. Other steps and parameters are the same as those in embodiment 1.
[0073] The mechanical properties and density of the lightweight alkali slag toughness material for cold region structural reinforcement prepared in Example 13 are as follows: 28d average compressive strength is 68.80MPa, 28d average flexural strength is 8.2MPa, and density is 1795kg / m 3 .
[0074] In Examples 1 to 13, the amounts of silica fume, fly ash, water-binder ratio, mortar-sand ratio, hollow glass microspheres and polypropylene fibers are screened, with the aim of examining the best performance of the lightweight alkali slag toughness material for cold region structure reinforcement prepared at what contents of silica fume, fly ash, water-binder ratio, mortar-sand ratio, hollow glass microspheres and polypropylene fibers.
[0075] Embodiment 14:
[0076] The preparation of the concrete reinforcement column using the lightweight alkali slag toughness material for cold region structure reinforcement in the present invention is specifically completed in the following steps:
[0077] Step 1: Tie up the steel cage, which consists of 4 HRB335 longitudinal bars with a diameter of 12 mm and 7 stirrups with a diameter of 6 mm;
[0078] Step 2: Use a large mixer to prepare ordinary concrete, then pour it into the formwork containing the steel cage until it covers the entire formwork;
[0079] Step 3: During the pouring process, vibrate with a vibrating rod, cover with engineering curing film after the vibrating is formed, and place in a normal temperature and humidity environment for curing;
[0080] Step 4: demoulding the cured concrete column and roughening its surface, placing the polished concrete column in a reinforcement mold, preparing a reinforcement layer according to the material ratios of Example 12 and pouring;
[0081] Step 5: Remove the molds of the cured reinforcement column and polish its surface. After these five steps, the reinforcement column made of lightweight alkali slag ductile material is completed and is qualified for axial compression and eccentric compression tests.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A lightweight alkali slag toughness material for cold region structure reinforcement, characterized by: The light alkali slag toughness material comprises the following components: industrial waste slag, potassium water glass, sodium hydroxide, fly ash, hollow glass microspheres, quartz sand, and polypropylene fiber; The mass ratio of industrial waste slag to potassium water glass is 1:0.248-0.286, the mass ratio of industrial waste slag to sodium hydroxide is 1:0.062-0.071, the mass ratio of industrial waste slag to silica fume is 1:0.067-0.231, the mass ratio of industrial waste slag to fly ash is 1:0.200-0.385, the water-binder ratio is 0.38, 0.42, 0.44, the water content of the composite water glass after the sodium hydroxide and potassium water glass are mixed is 0.4838, when calculating the water consumption, the water content of the composite water glass should be deducted, and quartz sand is added according to the mortar-sand ratio of 2:1, 1:1, 1:2, the volume content of the hollow glass microspheres is 10%-20%, and the volume content of the polypropylene fiber is 0%-0.2%.
2. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The industrial waste slag is one of slag, red mud, steel slag, phosphorus slag, coal gangue and slag-like powder or a mixture of several of them; the water is tap water or sea water.
3. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The potassium water glass has an initial modulus of 2.76, a Baume degree of 46.3, a SiO2 content of 28.15%, a K2O content of 15.98%, and a density of 1.465 g / m 3 .
4. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The silica fume is a by-product of large-scale industrial smelting. It has the appearance of gray or grayish white powder and a refractoriness of >1600°C. Its main chemical components are: SiO2, Al2O3, Fe2O3, MgO, CaO, and Na2O.
5. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The fly ash is secondary fly ash, which is the main solid waste discharged from coal-fired power plants. The residue on the 45μm square hole sieve is not more than 20%, the water requirement ratio is not more than 105%, the loss on ignition is not more than 8%, the water content is not more than 2%, the sulfur trioxide content is not more than 3%, and its main chemical components are: SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2.
6. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The quartz sand is refined quartz sand with a specification of 10 to 40 meshes.
7. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The hollow glass microsphere model is domestic hollow glass microsphere 60, white in appearance, and has a compressive strength of 12000 MPa.
8. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 1, characterized in that: The polypropylene fiber has a diameter of 12-20 μm and a length of 1-2 cm.
9. The lightweight alkali slag toughness material for cold region structure reinforcement according to claim 2, characterized in that: The preparation method of the slag-like powder is as follows: adding oxides to sea sand, calcining until it is melted, maintaining the slag-water ratio at 1:10-1:15 for water quenching and granulation, crushing the water-quenched slag, drying, grinding and sieving, and sieving to a powder with a residue of no more than 10%, thereby obtaining a slag-like powder, and the particle size of the slag-like powder is 35-40 μm; the oxide is one or more of SiO2, CaO, Al2O3, MgO, and Fe2O3; the mass ratio of sea sand to oxide is 3:1; and the calcination temperature is 650-700°C.
10. A method for preparing a lightweight alkali slag toughness material for cold region structure reinforcement as claimed in claim 1, characterized in that: The following steps are involved: S1. Weighing: Weigh the industrial waste slag to potassium water glass at a mass ratio of 1:0.248-0.286, the industrial waste slag to sodium hydroxide at a mass ratio of 1:0.062-0.071, the industrial waste slag to silica fume at a mass ratio of 1:0.067-0.231, and the industrial waste slag to fly ash at a mass ratio of 1:0.200-0.
385. The water-cement ratio is 0.38, 0.42, and 0.
44. The water content of the composite water glass after mixing sodium hydroxide and potassium water glass is 0.4838. When calculating the amount of water, the water content of the composite water glass should be deducted. The quartz sand is weighed at a cement-sand ratio of 2:1, 1:1, and 1:
2. The volume content of the hollow glass microspheres is 10%-20%, and the volume content of the polypropylene fiber is 0%-0.2%. S2, preparing mixed powder: Industrial waste residue, silica ash, fly ash, hollow glass microspheres, polypropylene fiber and quartz sand are mixed and stirred to obtain a mixed powder; S3. Adjust the modulus of potassium water glass: Under stirring conditions, pour sodium hydroxide into potassium water glass and let it stand for 1 to 2 hours to obtain a composite potassium water glass solution; S4. Place the mixed powder, composite potassium water glass solution, polypropylene fiber and water with different water-binder ratios in a mixer and stir them evenly, pour them into a steel mold, and then form them through high-frequency vibration on a concrete vibration table to obtain a lightweight alkali slag tough material for cold region structure reinforcement.